Unnatural narrative: A cognitive analysis of parallel and circular structures in flash fiction. - Karam, Khaled Mostafa; Shaaban, Areeg Nabil; Khalil, Hamdy Ebeid (Neohelicon, 2024)
Because of the growing popularity of novel forms of narrative, such as flash fiction, this study aims at expanding the parameters of cognitive narratology to encompass the interpretation of these unnatural and anti-mimetic narratives which disrupt the narrative conventions relying on inventive techniques. It adopts cognitive narratology and insights form cognitive linguistics to analyze how the unconventional narrative structures of flash fiction are encoded and decoded. It mainly focuses on how writers of flash fiction use parallel and circular structures to compress idea density and weighty significance into a sparce spatiotemporal scale which is compatible to the limits of cyberspace and decreasing attention span. It interprets the cognitive construction of these innovative structures and analyzes the cognitive processes promoted by reading them.